Hal-Hal Yang Ada Hubungannya Dengan Kematian Neonatal Di Beberapa Lokasi Di Wilayah Indonesia Periode Tahun 2011 Sampai Dengan Tahun 2019 - Nasir, Umi Kalsum; Rompegading, Andi Machmud (Bosowa Medical Journal, 2024)
Neonatal mortality is the death of a newborn in the first 28 days of life and the first 28 days is the most vulnerable period for survival. The purpose of this study was to find out things that have to do with neonatal mortality based on parity, antenatal care visit, prematurity, low birth weight, asphyxia. The research method used in this study is analytic by using a literature objective approach on things that have to do with neonatal mortality in the journal of medical research results in the literature. The results of research from ten literature journals show that there is a relationship between neonatal mortality in several locations in Indonesia from 2011 to 2019 it can be concluded that neonatal mortality, namely parity (p-value = <0.001), antenatal care visit (p-value = <0.001), prematurity (p-value = <0.001), low birth weight (p-value = <0.001), asphyxia (p-value = <0.001), had a significant relationship with neonatal mortality in several locations in Indonesia from 2011 to 2019. It is hoped that this research will be able to increase the participation of the health department, in collaboration with health workers and community leaders in preventing and dealing with neonatal mortality events